A comment on Manekin & Mitts 2022: Effective for Whom? Ethnic Identity and Nonviolent Resistance - Jan Fabian Dollbaum; Endre Borbáth; Jan Matti Dollbaum (Institute for Replication (I4R), 2023)
Manekin and Mitts (2022) investigate the success chances of minority ethnic groups when engaging in non-violent protests demanding political change. First, using observational data, the authors find that the success rate for nonviolent campaign tactics is lower for excluded/minority ethnic groups than for non-excluded/majority ethnic groups. Second, the authors use two original survey experiments to show that non-violent protest by ethnic minorities is perceived as more violent and requiring more policing than identical protest by majorities. This report reproduces the paper computationally and conducts several sensitivity analyses for both the observational and the experimental parts of the paper. We can confirm the general direction of the postulated effects, but evidence becomes less consistent (effect magnitudes and significance levels are not robust to some of the changes).
Keywords: 330; non-violence; group status; protest; social movement success; public opinion; discrimination; racism; minority groups